Correspondence & Conversations of Alexis de Tocqueville with Nassau William Senior from 1834 to 1859, Volume 2 - Tocqueville, Alexis de, 1805-1859; Senior, Nassau William, 1790-1864; Simpson, M. C. M. (Mary Charlotte Mair) (Salt Lake City, UT : Project Gutenberg, 2004)
"Correspondence & Conversations of Alexis de Tocqueville with Nassau William Senior" edited by M.C.M. Simpson is a collection of letters and dialogues documented over a span of years from the early to mid-19th century. This historical account delves into the political landscape and social theories of the time, particularly focusing on the events surrounding the French political upheaval and the rise of Louis Napoleon. The correspondence likely examines Tocqueville's reflections on democracy, tyranny, and the consequences of political decisions, providing insights into his profound philosophical insights as a thinker. At the start of the work, readers are introduced to the context of Tocqueville$1 (Bs thoughts, emerging from the backdrop of the tumultuous political environment of France post-1848 revolutions. The opening reveals Tocqueville$1 (Bs conversations with Nassau William Senior, where they discuss the military takeover by Louis Napoleon and the implications for French governance, civil liberties, and societal structures. Tocqueville emphasizes the unprecedented nature of this coup, highlighting the tension between the army and civilian governance, and reflects on the potential dangers of despotism ignited by fear of socialism. This initial exchange sets the tone for the subsequent letters and journals, positioning Tocqueville as a keen observer of the complexities of democracy and authoritarianism. (This is an automatically generated summary.)s
Release date is 2004-08-30
Produced by G. Graustein and PG Distributed Proofreaders. Produced from images provided by the Million Book Project
Keywords: France -- History -- Second Republic, 1848-1852; Tocqueville, Alexis de, 1805-1859; Tocqueville, Alexis de, 1805-1859 -- Correspondence; Senior, Nassau William, 1790-1864 -- Correspondence